2018
DOI: 10.3389/fpls.2018.00934
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Key Adaptation Traits in the Polyploid Perennial Medicago sativa Using GBS-SNP Mapping

Abstract: Understanding key adaptation traits is crucial to developing new cultivars with broad adaptations. The main objective of this research is to understand the genetic basis of winter hardiness (WH) and fall dormancy (FD) in alfalfa and the association between the two traits. QTL analysis was conducted in a pseudo-testcross F1 population developed from two cultivars contrasting in FD (3010 with FD = 2 and CW 1010 with FD = 10). The mapping population was evaluated in three replications at two locations (Watkinsvil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 58 publications
12
52
0
Order By: Relevance
“…The QTL analysis performed in this study revealed that some of the QTL associated with spring vigor were located at a similar region as those associated with fall dormancy and winter injury in previous studies [16,17]. Adhikari et al (2018) mapped four QTL associated with winter injury on chromosome Unfortunately, there was no QTL located in the same or similar interval to the QTL associated with fall dormancy in their study [17]. identified six QTL associated with fall dormancy on chromosomes 4, 6 and 7, and five QTL associated with winter injury on chromosomes 3 and 7 [16].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The QTL analysis performed in this study revealed that some of the QTL associated with spring vigor were located at a similar region as those associated with fall dormancy and winter injury in previous studies [16,17]. Adhikari et al (2018) mapped four QTL associated with winter injury on chromosome Unfortunately, there was no QTL located in the same or similar interval to the QTL associated with fall dormancy in their study [17]. identified six QTL associated with fall dormancy on chromosomes 4, 6 and 7, and five QTL associated with winter injury on chromosomes 3 and 7 [16].…”
Section: Discussionsupporting
confidence: 72%
“…This notion indicates that QTL mapping analysis of complex quantitative traits in alfalfa could be challenging and that large populations will be needed [33]. Compared with other QTL mapping populations in alfalfa [12,17] and other species [34,35], the population in our study was sufficiently large for the QTL mapping of spring regrowth vigor traits.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Brummer et al [10] and Lauriault et al [11] described other fall dormancy-rating as fall dormant (FD 1-3), semi-fall dormant (FD 4-6), non-fall dormant (FD 7-9), and extremely non-fall dormant (FD 10-11). Photoperiodism and air temperature in fall and throughout winter determine alfalfa fall dormancy which is related to plant growth, biomass accumulation and abiotic stresses tolerance of the alfalfa plant [7,[12][13][14][15]. Fall dormant alfalfa cultivars go dormant the earliest, have reduced shoot elongation in the fall and survive better throughout winter, whereas extremely non-fall dormant cultivars continue to grow, have the tallest plant height in the fall, and generally do not have good survival over the winter [16,17].Alfalfa forage productivity is impacted by its fall dormancy-rating that has correlation with forage nutritive value, plant survival, root characteristics, and persistence [8,[18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…In other words, the multi-environment QTL analysis is more accurate than singleenvironment experiment for the heterozygous perennial woody tree growth-related traits QTL mapping (El-Soda et al, 2014). Thus, to eliminate interference brought by environment and improve QTLs accuracy, the multi-environment QTL test in other environments using different backgrounds for Simao pine must be carried out in future Adhikari et al, 2018). Table 6 Quantitative trait loci (QTLs) for growth-related traits during 3 years in the mapping population The high-density linkage map of Simao pine A black bar indicates a SLAF marker.…”
Section: Discussionmentioning
confidence: 99%